Improvement of Erectile Dysfunction after Surgery for Cervical Disk Herniation - Fotakopoulos, George; Alexiou, George A.; Kotlia, Polixeni; Pachatouridis, Dimitrios; Voulgaris, Spyridon (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Erectile dysfunction (ED) has been previously reported in patients with cervical spondylotic myelopathy. After treatment, patients usually experience an improvement in sexual function. Herewith, we present a patient with cervical disc herniation at the C3-C4 and C5-C6 level with ED but without myelopathy. The patient underwent anterior microdiscectomy and fusion with cages. ED improved postoperatively. We propose that the presence of ED should be checked in patients with cervical disc herniation. Further studies are needed to clarify the incidence of ED in patients with cervical disc herniation.
Keywords: spine; cervical disc herniation; erectile dysfunction